EFFECTS OF GENDER ON STUDENTS’ ATTITUDE TO PHYSICS IN SECONDARY SCHOOLS IN OYO STATE, NIGERIA - Oba, Fatoba Joseph; Lawrence, Aladejana Alaba (European Scientific Journal, ESJ, 2014)
This study examined the effects of gender on students’ attitude in Physics in senior secondary schools in Oyo State, Nigeria. The participants for this study were 160 Senior Secondary School two (SSS2) students offering Physics in Ibadan, Oyo State. The selection was based on purposive sampling technique which involved four schools. Data collected by students’ attitude Physics scale (SAPS) were analysed using ANOVA. The Multiple classification analysis was used to explain the magnitude of the post Attitude of the different categories of the students. In line with the findings of this study, Gender was found to have no effect on Students’ Attitude but there was slight difference in Attitude of the students in favour of females. Therefore, stakeholders should put differences in the Attitude of males and females into consideration in the development and implementation of curriculum.